Kemerdekaan Belajar untuk Siswa: Studi Kritis dalam Perspektif Pedagogik Kritis - Wati Agustiani; Yusuf Tri Herlambang; Tatang Muhtar (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The concept of learning freedom for students has become fundamental for achieving learning freedom so that students have critical thinking, freedom of expression, and student independence, especially in the educational context. The aim of the research is to comprehensively examine the concept of freedom of learning which is oriented towards a critical study approach with a theoretical basis as a reference which is seen from the correlation of freedom of learning and critical pedagogy reviewed from the perspective of experts in building paradigms and implementing the concept, problems in implementation from freedom to learn, especially in Indonesia, as well as the importance of freedom to learn for society to create superior people. This research uses the literature study method to process and elaborate various critically selected studies so that they are relevant to the discussion raised, which will produce quality discussion. The results of the research studied show several things in the context of freedom of learning in education which has a fundamental portion in building several characters such as critical thinking, freedom of expression and student independence, this is still lacking in the final results because both the quality of learning and the teaching staff are not yet able to is at that level with various kinds of obstacles so that the implementation of freedom of learning is not yet effective. In reality, students are still objects in education so that students become passive consumers of communication. With this, it is hoped that the research that has been carried out will be able to make a contribution in inspiring and improving implementation using a pedagogical approach.